2014
DOI: 10.1007/s12282-014-0520-8
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity cardiac troponin I detection for 2 types of drug-induced cardiotoxicity in patients with breast cancer

Abstract: Background Breast cancer treatment with trastuzumab, a monoclonal antibody that targets human epidermal growth factor receptor type 2 (HER2), has largely been successful in improving the prognosis of HER2-positive disease. However, a critical issue associated with trastuzumab treatment is its cardiotoxic adverse effects, including cardiac insufficiency. Methods We measured levels of cardiac troponin I, a marker of myocardial damage, with a highly sensitive method (hs-cTnI) using a fully automated chemiluminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…In several cardiac biomarkers, only high-sensitive troponin assays are shown to detect not only immediately after the onset of acute myocardial infarction, but also poor cardiac prognosis of patients with cardiac failure or hypertension [14][15][16][17][18][19]. In regard to CTIC, several studies showed hs-TnI levels elevated after trastuzumab following anthracycline administration [11,12,23]. Conventional troponin T assays could not predict CTIC [13].…”
Section: Discussionmentioning
confidence: 99%
“…In several cardiac biomarkers, only high-sensitive troponin assays are shown to detect not only immediately after the onset of acute myocardial infarction, but also poor cardiac prognosis of patients with cardiac failure or hypertension [14][15][16][17][18][19]. In regard to CTIC, several studies showed hs-TnI levels elevated after trastuzumab following anthracycline administration [11,12,23]. Conventional troponin T assays could not predict CTIC [13].…”
Section: Discussionmentioning
confidence: 99%
“…Troponin is a polypeptide composed by three elements: troponin C (calcium binding), troponin I (actin-myosin binding), and troponin T (tropo-myosin binding); this protein complex has the contractile function in the cardiac striated muscle fibers, associated with actin and myosin. Tn I is present in the blood 4-8 h after clinical AMI, reaching a peak after 12-16 h and remaining detectable for 5-9 days [20]: this marker has a higher specificity, as compared to the rise of CK-MB [21]. The plasmatic increase of Tn I is therefore correspondent to a myocardial damage from acute coronary syndromes, AMI (Q and non-Q) and unstable angina, and it is associated with poor prognosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of cardiac troponin as measured by high-sensitivity assays is gaining acceptance for the prevention of cardiotoxicity associated with certain pharma-cotherapeutic regimens, particularly those used for cancer chemotherapy (15,16 ). Similarly, detection of even small cardiac troponin increases is an early sign of rejection of a transplanted heart and, consequently, serial cardiac troponin monitoring may guide timely modifications of immune suppression in heart transplant recipients (17 ).…”
Section: © 2015 American Association For Clinical Chemistrymentioning
confidence: 99%